STIGMA MASYARAKAT TERHADAP VAKSINASI COVID-19 DI WILAYAH KERJA PUSKESMAS BASO KABUPATEN AGAM TAHUN 2021 - Rahmat Syukri; Del Fatma Wati; Athiyya Gusman (HUMAN CARE JOURNAL, 2022)
Vaccination realization for the Baso community in Agam Regency is still low. Based on data from the West Sumatra Health Office until September 2021, Agam Regency occupies the last position in vaccination achievements among 19 regencies and cities of West Sumatra. Wrong stigma and lack of information are the cause of the lack of public compliance in participating in the Covid-19 vaccination program. Stigma as a phenomenon that can affect the individual as a whole. The purpose of this study was to explore how the stigma of the community in the working area of the Baso Public Health Center towards the Covid-19 vaccination facilitated by the government. This is a qualitative study using the deep interview method and a phenomenological study approach. Purposive sampling was used to select participants. The number of participants is 9 people from Baso. Data analysis using Collaizi approach. The study's finding revealed two themes: the rejection of the Covid-19 vaccination due to the crisis of public confidence in the side effects of the vaccine and the acceptance of the Covid-19 vaccination by the public were based on compulsion. It is hoped that with this research, the services provided by local health centers will be even better, especially in providing education or health education to the public regarding the Covid-19 vaccination.